1540‐nm fractional erbium: Glass laser is a safe and effective modality for nonablative facial rejuvenation. (1st February 2021) - Solomon‐Cohen, Efrat; Lapidoth, Moshe; Mimouni, Daniel; Akerman, Lehavit; Slodownik, Dan; Hodak, Emmilia; Levi, Assi
Abstract: Background: Laser treatments for facial rejuvenation are common, with ablative modalities being of more common use for this indication. Efficient nonablative modalities are of rising demand. Aim: Our aim was to determine the safety and efficacy of high‐fluence, nonablative 1540‐nm fractional Erbium:glass laser for facial rejuvenation. Patients and Methods: A retrospective study of patients treated with 3‐4 treatments using the 1540‐nm fractional Erbium:glass laser for facial rejuvenation, using 2500‐3000 mJ/stacked pulses (51‐61 mJ per pixel). Patients were followed‐up for 3 months following their last treatment. Before and after photos were independently blindly evaluated by 2 dermatologists, who graded them using a scale from 0 (exacerbation) to 4 (76%‐100% improvement) for 2 different facial regions (frontal face region and lateral canthal region). Pain perception and adverse effects as well as patient satisfaction were documented throughout the study. Results: Sixteen patients completed both treatment and follow‐up period. At the 3‐months posttreatment follow‐up visit, moderate‐to‐significant improvement in rhytids appearance (mean grade of improvement: 2.93 for frontal face and 3 for lateral canthal region) was observed. Patients' satisfaction was high (4.25). Patients reported mild and transient erythema posttreatment with no other adverse effects. Conclusion: The high‐fluence 1540‐nm fractional Erbium:glass laser is a safe and effective nonablative modality for facial rejuvenation.